Inequality of Economic Development Between Regions: A Case Study of Eastern and Western Indonesia - Hapsari Widayani; Syaiful Syaiful (PT. Publikasiku Academic Solution, 2026)
Indonesia faces persistent disparities in economic development between its western and eastern regions, a structural issue rooted in historical concentration of growth and investment. This study aims to analyze the magnitude and trends of economic development disparities between Eastern and Western Indonesia, identify the main factors causing these inequalities, and evaluate the impact of such disparities on regional welfare. The research employed a quantitative approach with secondary data from 2015-2023. Indicators include Gross Regional Domestic Product (GRDP), Human Development Index (HDI), poverty rate, and investment. Results show significant gaps where Western Indonesia's average GRDP per capita reaches Rp 65.4 million while Eastern Indonesia only Rp 38.7 million. Western Indonesia's HDI reaches 72.8 while Eastern Indonesia reaches 68.3. Eastern Indonesia's poverty rate 11.8% is higher than Western Indonesia's 8.2%. Main factors include investment concentration, limited infrastructure, and primary sector dependence. In conclusion, these disparities are widening over time and have negative impacts on social welfare and national integration. The study recommends investment redistribution, infrastructure development acceleration, and economic diversification to reduce disparities.